2022
DOI: 10.1186/s12917-022-03429-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma nucleosome concentrations in dogs with a variety of common cancers and in healthy dogs

Abstract: Background Cell free DNA, in the form of nucleosomes, is released into circulation during apoptosis and necrosis in a variety of diseases. They are small fragments of chromosomes that are composed of DNA wrapped around a histone core made of four duplicate histone proteins forming an octamer. The nucleosome compartment is a relatively uninvestigated area of circulating tumor biomarkers in dogs. The objectives of this study were to quantify and better characterize nucleosome concentrations in 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Q™ H3.1 Assay’ is designed for the detection of levels of histone H3.1-containing cfNucleosomes in human serum and has also been used to show that serum from canines with lymphoma contains a 7-fold-increased nucleosome level in their plasma relative to healthy control dogs [ 30 ]. Using this assay, a recent study quantified and characterised nucleosome concentrations in both healthy dogs ( n = 134) and those dogs with various cancer types ( n = 528) and found that tumours of haematopoietic origin were most likely to result in increased nucleosome concentrations in the plasma, whereas local tumours such as soft tissue sarcomas were the least likely to have this result [ 31 ]. However, it is important to note that the levels of nucleosomes can only be used for cancer detection in an otherwise clinically healthy dog, as other studies have shown that concentrations of nucleosomes are significantly higher in dogs under certain conditions relative to healthy controls, such as dogs with sepsis, with acute gastroenteropathies or following trauma [ 32 , 33 , 34 ].…”
Section: Methods For Sampling Tumour Cells In Dogsmentioning
confidence: 99%
“…Q™ H3.1 Assay’ is designed for the detection of levels of histone H3.1-containing cfNucleosomes in human serum and has also been used to show that serum from canines with lymphoma contains a 7-fold-increased nucleosome level in their plasma relative to healthy control dogs [ 30 ]. Using this assay, a recent study quantified and characterised nucleosome concentrations in both healthy dogs ( n = 134) and those dogs with various cancer types ( n = 528) and found that tumours of haematopoietic origin were most likely to result in increased nucleosome concentrations in the plasma, whereas local tumours such as soft tissue sarcomas were the least likely to have this result [ 31 ]. However, it is important to note that the levels of nucleosomes can only be used for cancer detection in an otherwise clinically healthy dog, as other studies have shown that concentrations of nucleosomes are significantly higher in dogs under certain conditions relative to healthy controls, such as dogs with sepsis, with acute gastroenteropathies or following trauma [ 32 , 33 , 34 ].…”
Section: Methods For Sampling Tumour Cells In Dogsmentioning
confidence: 99%
“…While cfDNA research on non-human animals is not as developed as in humans, there is increasing interest in the role of cfDNA as a biomarker as well as a tool to study pathophysiology in animals, especially companion animals. For example, several studies indicate the potential of implementing cfDNA tests in veterinary clinics for the minimally-invasive diagnosis and monitoring of cancer in dogs [ 471 , 472 , 473 , 474 , 475 , 476 , 477 ]. Furthermore, cfDNA may also serve as a potential marker of gastric dilatation–volvulus (GDV) [ 478 ] and immune-mediated hemolytic anemia (IMHA) [ 479 ], tissue injury [ 480 ], and sepsis [ 481 , 482 , 483 ] in dogs.…”
Section: Characterization Of Cfdna In Animalsmentioning
confidence: 99%
“…Biomarkers that could predict the response to treatment of different tumours with ECT or the combination of ECT with IL-12 GET have not yet been investigated in veterinary oncology. Nucleosome and ferritin concentrations and the LDH activity in blood have been shown to be valuable diagnostic biomarkers for various malignancies in animals [26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%